Mental Health in Adults with Non-communicable Diseases: An Overview - Sartika, Dona; Riana Putri, Prystia; Ayu Jeihan Fadhila, Nabella (Poltekkes Kemenkes Kupang, 2025)
Background: Non-communicable diseases (NCDs) are chronic conditions that progressively impair individuals’ health over time and may significantly affect mental well-being. Objectives: This study aimed to examine the mental health status of adults living with NCDs. Methods: A quantitative descriptive design was employed. The sampling technique used consecutive sampling with a sample size of 76 respondents aged 35-55 years, with a history of hypertension or diabetes mellitus (DM). The DASS 42 quistionnaire was used as a research instrument to collect data. In this study, univariate analysis with descriptive percentage was employed. Results: The results indicated that 25% of respondents experienced mild depression, 44.7% moderate anxiety, and 44.7% mild stress. Conclusions: NCDs may adversely affect the mental health of individuals. This needs to be followed up to mitigate the broader impact of NCDs, both on physical and mental health.